Purinergic neuron-to-glia signaling in the enteric nervous system - Gulbransen, Brian D. (Henry Stewart Talks, 2014)
The enteric nervous system is an extensive neural network that is housed in the wall of the gut and provides local control of gut functions, The environment within enteric ganglia is similar to brain tissue and only includes neurons and glia, Enteric glia a unique type of peripheral glia that share many similarities with astrocytes in the brain, Enteric glia are implicated in a number of essential processes in the intestine but recent evidence suggests that enteric glia are particularly integral in the regulation of purinergic communication between neurons in the enteric nervous system, Update interview: Inter- and intra-regional specializations, Update interview: Regulation of enteric neurocircuits, Update interview: Regulation of intestinal immune homeostasis, Update interview: Regulation of neuroinflammation and neuroplasticity following inflammation, Update interview: Regulation of development of visceral pain and dysmotility in disease
Updated at 2020/09/18